1998
DOI: 10.1086/306218
|View full text |Cite
|
Sign up to set email alerts
|

Pulsar Radio Emission by Conversion of Plasma Wave Turbulence: Nanosecond Time Structure

Abstract: The plasma wave turbulence emission mechanism is studied to make predictions for the temporal characteristics of pulsar radio emission. The turbulent emission process consists of a cycle of electrostatic wave growth and modulational conversion into radiative modes. The onset of plasma wave turbulence is marked by explosive spatial collapse of regions of high electric Ðeld and bursts of radiation. Intrinsic time structure is found on subnanosecond to 10 ns timescales. The pulse exhibits an unusual spectral sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
90
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(100 citation statements)
references
References 22 publications
10
90
0
Order By: Relevance
“…τ e ∼ 10 −10 s, very similar to the nano pulses proposed i.e. by Weatherall (1998) and also evident in the PIC-simulations of Jaroschek & Lesch (2006). The decay of the electric potential of a nano-pulse may be described by Φ(t) = Φ 0 · e −t/τ e with (t > 0).…”
Section: The Shape Of Pulsar Spectrasupporting
confidence: 84%
“…τ e ∼ 10 −10 s, very similar to the nano pulses proposed i.e. by Weatherall (1998) and also evident in the PIC-simulations of Jaroschek & Lesch (2006). The decay of the electric potential of a nano-pulse may be described by Φ(t) = Φ 0 · e −t/τ e with (t > 0).…”
Section: The Shape Of Pulsar Spectrasupporting
confidence: 84%
“…Observations by Hankins et al (2003) revealed that giant pulses at 5.5 GHz contain nanosecond wide subpulses and the presence of such narrow features has been predicted in numerical modelling by Weatherall (1998). At these frequencies the radio emission character of the Crab pulsar changes, with the interpulse emission becoming dominant.…”
Section: Introductionmentioning
confidence: 82%
“…The physical conditions there can be much different from the regions where radio emission is placed traditionally (i.e., at low altitudes and within a small range of heights dictated by radius-to-frequency mapping). This should be taken into account by the theories of GRP generation, for example, the ones that rely on plasma turbulence (Weatherall 1998) or on the interaction between the low-and high-frequency radio beams (Petrova 2006).…”
Section: Giant Pulsesmentioning
confidence: 99%